Objective understanding of the Nutri-score front-of-pack label by European consumers and its effect on food choices: an online experimental study - Manon Egnell; Zenobia Talati; Pilar Galan; Valentina A. Andreeva; Stefanie Vandevijvere; Marion Gombaud; Louise Dréano-Trécant; Serge Hercberg; Simone Pettigrew; Chantal Julia (BMC, 2020)
Abstract Background The effectiveness of Front-of-Pack nutrition Labels (FoPLs) may be influenced by national context. In light of the ongoing efforts to harmonize FoPLs across Europe, this study aimed to compare the effectiveness of five FoPLs (Health Star Rating system, Multiple Traffic Lights, Nutri-Score, Reference Intakes, Warning symbols) on consumer understanding and food choice in 12 European countries. Methods In 2018-2019, for three food categories, approximately 1000 participants per country were asked to select which food they would prefer to purchase between three products with distinct nutritional quality profiles, and then to rank the products by nutritional quality. Participants (N = 12,391 in total) completed these tasks first with no FoPL and then, after randomization to one of the five FoPLs, with a FoPL on the food packages. Associations between FoPLs and change in (i) nutritional quality of food choices and (ii) ability to correctly rank the products by nutritional quality were assessed with logistic regression models adjusted for sociodemographic and lifestyle characteristics of participants, conducted overall and by country. Findings Compared with the Reference Intakes, the Nutri-Score (OR = 3.23[2.75-3.81]; p < 0.0001), followed by the Multiple Traffic Lights (OR = 1.68[1.42-1.98]; p < 0.0001), was the most effective FoPL in helping consumers identify the foods' nutritional quality, overall and in each of the 12 countries. Differences between FoPLs regarding food choice modifications were smaller, but the effect of the Nutri-Score seemed slightly higher in eliciting healthier food choices overall compared with the Reference Intakes, followed by the Warning symbols, the Multiple Traffic Lights and the Health Star Rating system. Interpretation In the context of FoPL harmonization in Europe, these findings from an online experiment provide insights into the Nutri-Score's effectiveness on European consumers.